Rapid quantitative detection of Klebsiella pneumoniae in infants with severe infection disease by point-of-care immunochromatographic technique based on nanofluorescent microspheres - Chen, Ying; Sha, Lulu; Li, Wenqing; Zhou, Liuyan; Pei, Bing; Bian, Xinyu; Ji, Yongxin; Liu, Yiping; Wang, Li; Yang, Huan (Frontiers in Bioengineering and Biotechnology, 2023)
Klebsiella pneumoniae is one of the most important nosocomial pathogens that cause severe respiratory infections. As evolutionary high-toxic strains with drug resistance genes increase year by year, the infections caused by it are often accompanied by high mortality, which may be fatal to infants and can cause invasive infections in healthy adults. At present, the traditional clinical methods for detecting Klebsiella pneumoniae are cumbersome and time-consuming, and the accuracy and sensitivity are not high. In this study, nFM-based ICTS quantitative testing platform were developed for point-of-care detection of Klebsiella pneumoniae.Under optimum working conditions, the detection limits of PCR-GE, RTFQ-PCR, PCR-ICTS and SEA-ICTS are 7.7×10^(-3), 2.5×10^(-6), 7.7×10^(-6), 2.82×10^(-7) ng/μL, respectively. The SEA-ICTS and PCR-ICTS assays can quickly identify Klebsiella pneumoniae and could specifically distinguish Klebsiella pneumoniae samples from non-Klebsiella pneumoniae samples. Experiments show a diagnostic agreement of 100% between ICTS methods and the traditional clinical methods on the detection of clinical samples. During the purification process, the Silicon coated magnetic nanoparticles (Si-MNPs) were used to removed false positive results effectively from the products, which shows of great screening ability. The SEA-ICTS method was developed based on PCR-ICTS, which is a more rapid (45 minutes), low cost method compared with PCR-ICTS assay for the detection of Klebsiella pneumoniae in infants. Only need a cheap thermostatic water bath and takes a short detection time, this new method can potentially serve as an efficient POCT method for on-site detection of pathogens and disease outbreaks without fluorescent PCR instruments and professional technicians operation.